(untitled) (World Bulletin of Public Health, 2022)
Closed traumatic brain injury is quite common and affects millions of people worldwide every year. In the structure of injuries, the most dramatic is traumatic brain injury. In the European Union, up to 1.5 million people are hospitalized, 57,000 die every year due to TBI and three-quarters of them are young people. Kallidinogenase - tissue kallikrein, a component of the kallikrein - kinin system (KKS), has a protective effect against cerebral ischemia.